Laboratory manual in personal identification (dactyloscopy) - Revisa, William A.; Villaluz, Joner C.; Pecson, Reymert L. (Philippines; Wisemans Books Trading, 2021)
"The approach of the manual is simplified to aid students in the learning process and to hone their skills to become effective law enforcers and criminalists in the future".
English Text.
Keywords: Fingerprints -- Laboratory manuals